Tái sử dụng phần mềm trong tin học quản lí - Thành, Phạm Đức (Journal of Computer Science and Cybernetics, 2016)
Reuse of products is certainly not a new concept. However, with software cost estimated have reached billions VND,even a modest productivity gain through reuse translates into tremendous savings. Reuse can contribute to productivity gains in the followings way: achiving shorter development time, increasing software reliability and ensuring enhanced maintaibility. This paper presents some lessons and explains the use of domain analysis as a method to select reusable components and the various components of a reusable component.